Patterns of Whole-Body Vibrations in Open Pit Mining - Cristina Bernardo (2014)
The main objective is to detect Whole-Body Vibration (WBV) patterns in different mining equipments along their working cycles. Three activities / equipment were studied (rock drill, shovel and dumper) in a north Portugal quarry. The WBV measurement and analysis was conducted in accordance with ISO 2631-1 (1997). It was studied three WBV transmission ways: 1) seat surface, 2) seat backrest and 3) cabin floor (feet). Rock drill shown a WBV pattern, where there was an extensive drilling phase, with residual accelerations values, and a short phase when the vehicle have to move to do another hole. In shovel, was not detected any associated pattern. In dumper, can be distinguished all tasks: loading, loaded and unloaded travel, dumping. Big differences were found when WBV is transmitted through the seat backrest, with the longitudinal x-axis dominating. Rock drill and dumper shown WBV patterns, as opposed to shovel.